Patients With Chronic Pain: The Aspect Of Negative Body Image - Kieselbach, Kristin; Fauler, Ingrid; Abberger, Birgit (PPmP - Psychotherapie · Psychosomatik · Medizinische Psychologie, 2024)
Objective Negative body image is an increasingly important factor in chronic pain disorders; particularly because the two conditions mutually influence each other. Our study examines body-image-related attitudes and comorbid psychic symptoms in patients with chronic pain disorders.Methods and Measures 188 patients with chronic pain answered the Dresden body image questionnaire (DKB-35), the Hospital Anxiety and Depression Scale (HADS) and the Beck’s Depression Inventory (BDI).Results The mean values of the DKB-35 subscales range between 2.24 und 3.29. The subscale “vitality” has the lowest mean value. BDI and HADS correlated significantly with the DKB-35 subscales. The subscale “body-acceptance” intercorrelated high with the two subscales “vitality” and “self-aggrandizement”.Conclusion Our findings verify that chronic pain is strongly associated with negative body image. The issues of vitality and psychological symptoms seem particularly central in this complex interaction. The biopsycho-social model and the avoidance-endurance approach to chronic pain offer important ideas for explanation and treatment.
Keywords: chronic pain; negative body image; vitality; bio-psycho-social model; avoidance-endurance model